Hydrographic Data Bases for Tidal Numerical Models - George, K. J. (The International Hydrographic Review, 2015)
Bathymetric data for tidal numerical models may be organised either as a list of soundings located in space, or as a table of average depths in rectangular areas which correspond to the cells used in the model. The techniques of averaging used in the second method are described, and its accuracy is examined. Details are given of its operation in the case of the author’s tidal numerical models.